ANALISIS MANAJEMEN DAN MUTU PENDIDIKAN DI BUSTANUL ATHFAL GEMBLEGAN I KALIKOTES: UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN - Ambar Winarti; Agus Murtana; Mawardi, Mawardi (Bajang Institute, 2025)
This research aims to explore and describe the principal’s contribution in managing and enhancing the quality of education at Bustanul Athfal (BA) Gemblegan 1 Kalikotes, Klaten. A descriptive qualitative design was applied, with data gathered through in-depth interviews and observations focusing on the principal as the main informant. The results show that the principal plays an active and strategic role in different aspects of school management, such as teachers and staff, students, facilities, and other supporting components. Moreover, the principal fulfills several crucial roles in improving quality, including educator, manager, administrator, supervisor, leader, innovator, and motivator. These functions significantly contribute to the institution’s progress towards better educational standards